Prognostic Factors for Overall Survival in Patients with Hormone Receptor‐Positive Advanced Breast Cancer: Analyses From PALOMA‐3. (12th June 2021) - Rugo, Hope S.; Cristofanilli, Massimo; Loibl, Sybille; Harbeck, Nadia; DeMichele, Angela; Iwata, Hiroji; Park, Yoon Hee; Brufsky, Adam; Theall, Kathy Puyana; Huang, Xin; McRoy, Lynn; Bananis, Eustratios; et al.
Abstract: Background: This analysis investigated whether baseline characteristics affect the survival benefit derived from palbociclib‐fulvestrant and the optimal timing of cyclin‐dependent kinase 4/6 inhibitor therapy for advanced breast cancer (ABC) in patients from PALOMA‐3. Patients and Methods: In total, 521 patients were randomized 2:1 to receive palbociclib (125 mg/day, 3/1 schedule)–fulvestrant (500 mg, intramuscular injection, on days 1 and 15 of cycle 1, and then day 1 of each subsequent cycle) or matching placebo‐fulvestrant. Median overall survival (OS) and progression‐free survival were estimated using the Kaplan‐Meier method. Results: Multivariable analysis identified endocrine sensitivity, nonvisceral disease, no prior chemotherapy for ABC, and Eastern Cooperative Oncology Group performance status (ECOG PS) of 0 as significant prognostic factors for OS. Patients without chemotherapy for ABC had fewer prior lines of treatment in any setting and in the ABC setting versus patients with prior chemotherapy for ABC (two or fewer prior systemic therapies: 69% vs. 42%; no more than one prior line for ABC: 82% vs. 33%, respectively). Median OS was prolonged with palbociclib‐fulvestrant in patients without prior chemotherapy for ABC (39.7 vs. 29.5 months; hazard ratio, 0.75; 95% confidence interval [CI]: 0.56–1.01) and was similar in patients with prior chemotherapy for ABC (25.6 vs. 26.2 months; hazard ratio, 0.91 [95% CI: 0.63–1.32]) versus placebo‐fulvestrant. Conclusion: Prognostic factors for OS included endocrine sensitivity, nonvisceral disease, ECOG PS of 0, and no prior chemotherapy for ABC. Exploratory analyses suggest improved OS with palbociclib‐fulvestrant versus placebo‐fulvestrant in patients with no prior chemotherapy for ABC, prior endocrine sensitivity, and fewer prior regimens of systemic therapy. ( Clinical trial identification number : NCT01942135). Implications for Practice: Prognostic factors for overall survival in HR+/HER2− advanced breast cancer (ABC) include the absence of prior chemotherapy in the advanced setting, endocrine sensitivity, nonvisceral disease, and an ECOG performance status of 0. Improved overall survival benefit was observed with palbociclib‐fulvestrant versus placebo‐fulvestrant in patients (regardless of menopausal status or visceral involvement) with no prior chemotherapy for ABC, with prior endocrine sensitivity, and fewer prior regimens of systemic therapy. Progression‐free survival was prolonged with palbociclib across subgroups (regardless of chemotherapy exposure in ABC). These exploratory findings suggest that patients may receive greater clinical benefit from palbociclib‐fulvestrant if they receive the combination before chemotherapy in the advanced setting. Abstract : This article focuses on whether baseline characteristics affect the survival benefit derived from palbociclib‐fulvestrant and the optimal timing of cyclin‐dependent kinase 4/6 inhibitor therapy for advanced breast cancer in patients from the PALOMA‐3 clinical trial.